(untitled) (Journal of Contemporary Philology, 2024)
Yasmina Reza (1959) is one of the most important and most staged contemporary playwrights. Her plays, translated into more that 35 languages, are produced in the most famous theatres worldwide. The object of analysis of this paper is “Art” (1994), the most performed French play in the World, right after Molière’s plays. Paradoxically, the very popularity and success of the play has for long been the reason for the French theatre critique considering it an entertainment theatre or boulevard theatre. Today, however, “Art” and Reza’s approach to playwriting are subjects of a number of theatrical analyses and re-readings that recognize their multi-layered qualities and formal innovation, seeing them as a continuation of the avant-garde theatre. This paper focuses on the deconstruction of the traditional dramatic categories, as well as on undermining the division between “amusement” and “art”, which are in the hearth of this “comedy” that impresses with its complex and refined dramatic construction, with the universality and the seriousness of the topics that it treats under the veil of lightness.